MEKANISME PEMOTONGAN DAN PELAPORAN PAJAK PENGHASILAN PASAL 21 SECARA E-FILING ATAS PEGAWAI PADA KANTOR KEPALA DESA SIRAP KECAMATAN JUAI KABUPATEN BALANGAN - Hasanah, Maulidatul; Rano Wijaya; Ikhwan Faisal (JRUP: JURNAL REFERENSI DAN ULASAN PERPAJAKAN, 2022)
The purpose of this research is to find out how employees at the Sirap Village Head's Office can withhold and report Income Tax (PPh) Article 21 via e-filing. In this research, secondary data was obtained in the form of salaries paid to employees at the Sirap Village Head's Office. The type of information obtained in the written research is quantitative and qualitative information, while the sources for collecting information in this research come from the Head of Sirap Village and the Head of Financial Affairs at the Office of the Head of Sirap Village using the interview method. Apart from interviews, data collection in this research also used observation by paying attention to the notes and evidence of the Head of Financial Affairs at the Sirap Village Head's Office which was linked to Income Tax (PPh) Article 21 and linked to the commitment of the Sirap Village Head's Office to Income Tax (PPh). ) Article 21. Researchers focus on withholding and reporting Article 21 Income Tax (PPh) on employees in this research, so that this does not spread and leads to clear resu